2015
DOI: 10.1001/jamadermatol.2015.0810
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cancer Diagnosis With Reflectance Confocal Microscopy

Abstract: The study highlights key RCM diagnostic criteria for melanoma and basal cell carcinoma that are reproducibly recognized among RCM users. Diagnostic accuracy increases with experience. The higher accuracy of majority diagnosis suggests that there is intrinsically more diagnostic information in RCM images than is currently used by individual evaluators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…Specificity for pink naevi excluding spitz naevi (R2: 55.3%; R3: 58.9%) showed significant improvement over dermoscopy only evaluation (35.7%) verifying that RCM permits visualization of morphologic features providing more cellular information for the reader and therefore the potential to improve both diagnostic accuracy and confidence in this group of equivocal lesions. In the SK/SL/LPLK/AK category specificities (R2: 48.4%; R3: 36.4%) were acceptable and also in concordance with literature [1013]. The low specificity for recognizing spitz naevi (R2: 25.0%; R3: 12.5%) confirms previously reported limitations of RCM application in this subset of lesions [23].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Specificity for pink naevi excluding spitz naevi (R2: 55.3%; R3: 58.9%) showed significant improvement over dermoscopy only evaluation (35.7%) verifying that RCM permits visualization of morphologic features providing more cellular information for the reader and therefore the potential to improve both diagnostic accuracy and confidence in this group of equivocal lesions. In the SK/SL/LPLK/AK category specificities (R2: 48.4%; R3: 36.4%) were acceptable and also in concordance with literature [1013]. The low specificity for recognizing spitz naevi (R2: 25.0%; R3: 12.5%) confirms previously reported limitations of RCM application in this subset of lesions [23].…”
Section: Discussionsupporting
confidence: 87%
“…A recent study showed that sensitivity is higher for experienced RCM users versus those who are new to the field (91.0% vs. 84.8%), but that specificity is quite similar (80.0% vs. 77.9%) [13]. In our study single reader dermoscopy-RCM image set evaluation was comparable with recently published literature showing that RCM has a high overall sensitivity for pink cutaneous lesions (R2: 91.3%; R3: 96.5%) [1012,14,15,23].…”
Section: Discussionmentioning
confidence: 99%
“…The RCM features included: cord-like structures, tumor nests, palisading, streaming, dark peri-tumoral rim (clefting), stroma with plump cells and bright dots, and horizontal vessels, 13,14,16,2729 while OCT features were: hyporeflective/gray structures attached to the dermal-epidermal junction (DEJ), disruption of the DEJ, hyporeflective/gray ovoid structures in the dermis, dark peri-tumoral rim (clefting), hyper-reflective peritumoral stroma, hyper-reflective streaks and branched vessels. 12,3032 …”
Section: Methodsmentioning
confidence: 99%
“…Other studies have shown good correlation between RCM and histopathology for melanocytic pathologies under different circumstances, 9,17 but difficulties with correlation in the dermal layer. 18 Secondly, there was no guarantee that RCM images were taken from where the DM was identified histologically within the specimen. While this would be desirable in a prospective study design, because DM is rare, it may be difficult to undertake.…”
Section: Discussionmentioning
confidence: 99%